Antibodies to Aedes aegypti D7L salivary proteins as a new serological tool to estimate human exposure to Aedes mosquitoes - Chea, Sophana; Willen, Laura; Nhek, Sreynik; Ly, Piseth; Tang, Kristina; Oristian, James; Salas-Carrillo, Roberto; Ponce, Aiyana; Leon, Paola Carolina Valenzuela; Kong, Dara; Ly, Sokna; Sath, Ratanak; et al. (Frontiers in Immunology, 2024)
Aedes spp. are the most prolific mosquito vectors in the world. Found on every continent, they can effectively transmit various arboviruses, including the dengue virus which continues to cause outbreaks worldwide and is spreading into previously non-endemic areas. The lack of widely available dengue vaccines accentuates the importance of targeted vector control strategies to reduce the dengue burden. High-throughput tools to estimate human-mosquito contact and evaluate vector control interventions are lacking. We propose a novel serological tool that allows rapid screening of human cohorts for exposure to potentially infectious mosquitoes. We tested 563 serum samples from a longitudinal pediatric cohort study previously conducted in Cambodia. Children enrolled in the study were dengue-naive at baseline and were followed biannually for dengue incidence for two years. We used Western blotting and enzyme-linked immunosorbent assays to identify immunogenic Aedes aegypti salivary proteins and measure total anti-Ae. aegypti IgG. We found a correlation (rs=0.86) between IgG responses against AeD7L1 and AeD7L2 recombinant proteins and those to whole salivary gland homogenate. We observed seasonal fluctuations of AeD7L1+2 IgG responses and no cross-reactivity with Culex quinquefasciatus and Anopheles dirus mosquitoes. The baseline median AeD7L1+2 IgG responses for young children were higher in those who developed asymptomatic versus symptomatic dengue. The IgG response against AeD7L1+2 recombinant proteins is a highly sensitive and Aedes specific marker of human exposure to Aedes bites that can facilitate standardization of future serosurveys and epidemiological studies by its ability to provide a robust estimation of human-mosquito contact in a high-throughput fashion.